2020
DOI: 10.24815/siele.v7i2.16788
|View full text |Cite
|
Sign up to set email alerts
|

Instruments’ validation of access to motivation, skills, and use of digital technology: EFL context in Indonesia

Abstract: The purpose of this study was to validate instruments regarding digital technology access among Indonesian English as a Foreign Language (EFL) faculty members during the Corona Virus Disease 2019 (COVID-19). An EFL Faculty member’s Access to Digital Technology (EFL-FADT) scale was adopted from previous relevant studies consisting of Motivation, Skills, and Use. A total of 235 EFL faculty members from three public and three private universities in Indonesia participated in this study, selected through cluster r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
2
3
0
Order By: Relevance
“…Later on, with the demand of the current distant learning and online education process, it needs integral development of research competence and digital literacy. This issue becomes more significant related to integrating the technology during the pandemic era (Prasojo et al, 2020). This finding supports the results of previous studies that showed how research activities develop students' content knowledge and research, although they can perceive several problems during the process.…”
Section: B the Model Of Research Competence Critical Thinking And Dig...supporting
confidence: 88%
“…Later on, with the demand of the current distant learning and online education process, it needs integral development of research competence and digital literacy. This issue becomes more significant related to integrating the technology during the pandemic era (Prasojo et al, 2020). This finding supports the results of previous studies that showed how research activities develop students' content knowledge and research, although they can perceive several problems during the process.…”
Section: B the Model Of Research Competence Critical Thinking And Dig...supporting
confidence: 88%
“…The findings of this study were corroborated by several previous studies conducted by other researchers, including Prasojo et al's research [17], which shares similar instrument validity characteristics with this study. However, Prasojo et alfocus on instrument validity in terms of motivation, ability, and use of digital technology.…”
Section: F Results Of Final Instrumentsupporting
confidence: 92%
“…The academic findings of the current study herein are noteworthy due to the limited research in recognizing the behavioral factors of students' intention to choose an educational administration major for their study in higher institutions. As a result, the valid and reliable scale proposed in this study produces a strong baseline providing solutions to the natural research problems based on the hypothesis elaboration and evaluation [35], [36]. The current study's findings indicate that SN (H1) influences students' intentions to major in educational administration.…”
Section: Discussionmentioning
confidence: 59%